Nutritional comparison between dried and ensiled indigofera, papaya and moringa leaves - Jayanegara, A.; Ardani, V.; Sukria, H. A. (Diponegoro University, 2019)
The objective of this experiment was to evaluate chemical composition, in vitro fermentation and digestibility of dried and ensiled indigofera, papaya and moringa leaves. The leaves were subjected to artificial drying in an oven at 60oC for 24 h and ensiling treatment for 30 d under room temperature. Dried and ensiled samples were determined for chemical composition, silage fermentation characteristics and in vitro rumen fermentation and digestibility. The experimental design was a factorial design 3 × 2 in which the first factor was different leaves (indigofera, papaya and moringa) and the second factor was conservation treatments (drying and ensiling). Determination of chemical composition was performed in duplicate whereas in vitro evaluation was conducted in three replicates. Results showed that ensiling treatment decreased CP contents of indigofera and moringa but not papaya leaves. Ensiling also decreased NDF and NDICP contents of all experimental leaves in comparison to drying treatment. The pH of all silages was high and they were characterized with high ammonia concentrations. Ensiled indigofera tended to have lower IVDMD and IVOMD as compared to dried indigofera (P<0.1). It can be concluded that ensiling of high protein forages leads to considerable extent of proteolysis.